The role of type traits of dairy cattles in long productive life - Berta, Attila; Béri, Béla (Acta Agraria Debreceniensis, 2006)
In the last few decades, a new intensive milking stock has developed as a result of breed-converter crossing in Hungary. Additionally, the reproduction biology of the population was adversely affected by keeping and feeding technologies. Productive lifetime has shortened and the service period has lengthened. However, profitable milk production requires cows with longer productive lives and larger life-time productions. In our study, we made a comparison between production, culling causes, and type traits of culled Holstein Friesian cows after first calving and of cows with a minimum of eight lactations. We established that the first lactation production of cows with longer productive lives was more or less homogeneous. Disease of metabolism as well as digestive and respiratory problems, were the main causes of the culling of cows with short productive lives, and reproduction and udder problems as well as low production, were the main causes of the culling of cows with long productive lives. We found a significant difference in the distributions of strength, body depth, dairy form, croup width, rear leg side view, foot angle, fore udder attachment and teat placement between the two groups. Furthermore, we established that cows with lower stature, less strength, a somewhat deeper body, better dairy form, narrower croup width, smaller foot angle, looser fore udder attachment and some outside teat placement had longer productive lives.